Baicalin and Baicalein Inhibit Src Tyrosine Kinase and Production of IL-6 - Dubravko Jelić; Agnieszka D. Lower-Nedza; Adelheid H. Brantner; Biljana Blažeković; Baolin Bian; Jian Yang; Karmen Brajša; Sanda Vladimir-Knežević (Journal of Chemistry)
Flavonoids play an important role in the treatment of various diseases, as they are able to inhibit reactive oxygen species, which cause damage to cells and tissues which may lead to increased risk of inflammatory diseases. Baicalin and baicalein, two flavonoids found in the roots of Scutellaria baicalensis, in the leaves of Thymus vulgaris and Oroxylum indicum, were tested for their anti-inflammatory activity as well as for their cytotoxicity. Thereby the two compounds were investigated on Src tyrosine kinase inhibition and inhibition of production of interleukin (IL-6) in lipopolysaccharide- (LPS-) stimulated THP-1 cells. Additionally, the THP-1 cell line was used for the determination of the cytotoxicity. Both baicalin and baicalein showed some anti-inflammatory properties, while baicalein turned out to be the more active compound with higher inhibitory activities on both Src tyrosine kinase and production of cytokine IL-6. Baicalin and baicalein showed no signs of cytotoxicity in the MTS cytotoxicity assay in THP-1 cells.